Body composition in male lifelong trained strength, sprint and endurance athletes and healthy age-matched controls - Walker, Simon; von Bonsdorff, Mikaela; Cheng, Sulin; Häkkinen, Keijo; Bondarev, Dmitriy; Heinonen, Ari; Korhonen, Marko T. (Frontiers in Sports and Active Living, 2023)
Introduction Aging involves many physiological processes that lead to decreases in muscle mass and increases in fat mass. While regular exercise can counteract such negative body composition outcomes, masters athletes maintain high levels of exercise throughout their lives. This provides a unique model to assess the impact of inherent aging. The present study compared lean mass and fat mass in young and masters athletes from different sports to age-matched non-athletic individuals. Methods Participants included young (20–39 years, n = 109) and older (70–89 years, n = 147) competitive male athletes, and 147 healthy age-matched controls (young = 53, older = 94 males). Athletes were separated into strength (e.g., weightlifters, powerlifters), sprint (e.g., sprint runners, jumpers) and endurance (e.g., long-distance runners, cross-country skiers) athletic disciplines. Body composition was assessed by dual-energy x-ray absorptiometry (DXA). Upper and lower limb lean mass was combined for appendicular lean mass as well as appendicular lean mass index (ALMI; kg/m2). Individuals’ scores were assessed against established cut-offs for low muscle mass, obesity, and sarcopenic obesity to determine prevalence in each group. Results ALMI was greater in young strength (0.81–2.36 kg/m2, ∼15% and 1.24–2.74 kg/m2, ∼19%) and sprint (95% CI = 0.51–1.61 kg/m2, ∼11% and 0.96–1.97 kg/m2, ∼15%) athletes than in endurance and controls, respectively (all P < 0.001). In masters athletes, only strength athletes had greater ALMI than endurance athletes, but both older strength and sprint athletes had greater ALMI than older controls (0.42–1.27 kg/m2, ∼9% and 0.73–1.67 kg/m2, ∼13%, respectively, both P < 0.001). Fat mass was significantly lower in sprint and endurance athletes compared to strength athletes and controls in both age-groups. Sarcopenic obesity was identified in one young (2%) and eighteen (19%) older controls, while only two older endurance athletes (3%) and one older strength athlete (2%) were identified. Discussion Lifelong competitive sport participation leads to lower prevalence of sarcopenic obesity than a recreationally active lifestyle. This is achieved in strength athletes by emphasizing muscle mass, while sprint and endurance athletes demonstrate low fat mass levels. However, all older athlete groups showed higher fat mass than the young groups, suggesting that exercise alone may not be sufficient to manage fat mass.